Low copy numbers of complement C4 and C4A deficiency are risk factors for myositis, its subgroups and autoantibodies - Zhou, Danlei; King, Emily H; Rothwell, Simon; Krystufkova, Olga; Notarnicola, Antonella; Coss, Samantha; Abdul-Aziz, Rabheh; Miller, Katherine E; Dang, Amanda; Yu, G Richard; Drew, Joanne; Lundström, Emeli; et al. (Annals of the rheumatic diseases, 2023)
BACKGROUND: Idiopathic inflammatory myopathies (IIM) are a group of autoimmune diseases characterised by myositis-related autoantibodies plus infiltration of leucocytes into muscles and/or the skin, leading to the destruction of blood vessels and muscle fibres, chronic weakness and fatigue. While complement-mediated destruction of capillary endothelia is implicated in paediatric and adult dermatomyositis, the complex diversity of complement C4 in IIM pathology was unknown. METHODS: We elucidated the gene copy number (GCN) variations of total C4, C4A and C4B, long and short genes in 1644 Caucasian patients with IIM, plus 3526 matched healthy controls using real-time PCR or Southern blot analyses. Plasma complement levels were determined by single radial immunodiffusion. RESULTS: The large study populations helped establish the distribution patterns of various C4 GCN groups. Low GCNs of C4T (C4T=2+3) and C4A deficiency (C4A=0+1) were strongly correlated with increased risk of IIM with OR equalled to 2.58 (2.28-2.91), p=5.0×10-53 for C4T, and 2.82 (2.48-3.21), p=7.0×10-57 for C4A deficiency. Contingency and regression analyses showed that among patients with C4A deficiency, the presence of HLA-DR3 became insignificant as a risk factor in IIM except for inclusion body myositis (IBM), by which 98.2% had HLA-DR3 with an OR of 11.02 (1.44-84.4). Intragroup analyses of patients with IIM for C4 protein levels and IIM-related autoantibodies showed that those with anti-Jo-1 or with anti-PM/Scl had significantly lower C4 plasma concentrations than those without these autoantibodies. CONCLUSIONS: C4A deficiency is relevant in dermatomyositis, HLA-DRB1*03 is important in IBM and both C4A deficiency and HLA-DRB1*03 contribute interactively to risk of polymyositis.
Keywords: dermatomyozitida; myozitida; Genetic Predisposition to Disease; DNA Copy Number Variations; Risk Factors; Autoantibodies; HLA-DRB1 Chains; Child; Complement C4a; dítě; Adult; dospělí; variabilita počtu kopií segmentů DNA; Myositis; komplement 4; HLA-DRB1 řetězec; komplement C4a; lidé; HLA-DR3 antigen; autoprotilátky; Humans; rizikové faktory; HLA-DR3 Antigen; Dermatomyositis; genetická predispozice k nemoci; Complement C4